Effect of Aromatherapy using Lavender Oil on Audio and Visual Reaction Time: A Quasi-experimental Study - Saroj Chaudhary; Manjinder Kaur; Suman Sharma; Naren Kurmi; Khushboo Shrimali; Soniya Pipliwal; Muskan Singh (Journal of Clinical and Diagnostic Research)
Introduction: Recently, the aromatheraphy has been a topic of interest in field of research and is reported to exert psychomodulatory effects through the limbic system. Lavender oil is widely researched for its effects on nervous system and shows calming effects. Aim: To evaluate Auditory Reaction Time (ART) and Visual Reaction Time (VRT) after 30 minutes of inhalational of lavender oil. Materials and Methods: This quasi-experimental study was conducted on 30 healthy volunteers after obtaining the clearance from ethics committee and informed consent from the participant. The audiovisual time was recorded twice for each subject, before and after the intervention i.e., 30 minutes of inhalation of lavender oil using aroma lamp. The data was analysed using Statistical Package for the Social Sciences (SPSS) version 20.0. Results: The present study showed significant prolongation of both ART and VRT (p-value=0.04 and 0.01, respectively) after 30 minutes inhalation of lavender oil from pre-exposure value of ART increased from 0.76±0.25 msec to 0.91±0.31 msec and VRT increased from 0.62±0.20 msec to 0.74±0.18 msec was observed. Conclusion: The prolongation of ART and VRT indicates the inhibitory effect of the inhalational lavender oil on the central neuron especially in the limbic system, through the activation of GABA (gamma-aminobutyric acid) receptors. Hence, it results in calming effect on the brain, inducing relaxation and sedation.